2004
DOI: 10.4049/jimmunol.172.6.3822
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the D Prostanoid Receptor 1 Regulates Immune and Skin Allergic Responses

Abstract: The mobilization of Langerhans cells (LCs) from epithelia to the draining lymph nodes is an essential process to initiate primary immune responses. We have recently shown that in mice, PGD2 is a potent inhibitor of epidermal LC emigration. In this study, we demonstrate that activation of the D prostanoid receptor 1 (DP1) impedes the TNF-alpha-induced migration of human LCs from skin explants and strongly inhibits the chemotactic responses of human LC precursors and of maturing LCs to CC chemokine ligands 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 62 publications
1
89
0
Order By: Relevance
“…These data are generally consistent with the results of our metabolism studies. PGD 2 and its receptors, DP and CRTH2, are known to be involved in chronic allergic skin inflammation (Angeli et al, 2004;Satoh et al, 2006). The marked increases in PGFS and PGIS that we noted in response to UVB also suggest that eicosanoids produced by these enzymes may be important mediators of cutaneous inflammation (Muller et al, 2000;Takahashi et al, 2002).…”
Section: Discussionsupporting
confidence: 51%
“…These data are generally consistent with the results of our metabolism studies. PGD 2 and its receptors, DP and CRTH2, are known to be involved in chronic allergic skin inflammation (Angeli et al, 2004;Satoh et al, 2006). The marked increases in PGFS and PGIS that we noted in response to UVB also suggest that eicosanoids produced by these enzymes may be important mediators of cutaneous inflammation (Muller et al, 2000;Takahashi et al, 2002).…”
Section: Discussionsupporting
confidence: 51%
“…We have reported that PGD 2 inhibits the migration of maturing DC via DP1 [9,14,15] whereas it increases the chemokinetic activity of DC precursors through DP2 [11]. Moreover, PGD 2 profoundly modulates the immunoregulatory capacity of DC via DP1 [11,16].…”
Section: Introductionmentioning
confidence: 98%
“…PGD 2 is widely distributed in rat and human brain (Abdel-Halim et al 1977;Narumiya et al 1982;Ogorochi et al 1984). In peripheral tissues, PGD 2 executes a wide range of functions, including vasodilatation, inhibition of platelet aggregation, glycogenolysis, vasoconstriction, allergic reaction mediation, and intraocular pressure reduction (Whittle et al 1983;Narumiya and Toda 1985;Casteleijn et al 1988;Sturzebecher et al 1989;Darius et al 1994;Matsugi et al 1995;Matsuoka et al 2000;Angeli et al 2004). In the brain, PGD 2 has been shown to contribute to sleep induction, modulation of body temperature, olfactory function, hormone release, nociception, and neuromodulation (Eguchi et al 1999;Urade and Hayaishi 1999;Mizoguchi et al 2001;Hayaishi 2002;Hayaishi and Urade 2002;Gelir et al 2005).…”
mentioning
confidence: 99%
“…Furthermore, it has been documented that its activation decreases cAMP and increases intracellular calcium levels (Bohm et al 2004;Sandig et al 2006). The in vivo role of DP1 in the peripheral nervous system has been well investigated (Angeli et al 2004;Hata and Breyer 2004;Koch et al 2005), but our knowledge of its role in the brain is still very limited (Campbell and Feinberg 1996;Urade and Hayaishi 1999;Hayaishi and Urade 2002;Obal and Krueger 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation